Actual problems of modern journalism - Ahmet, A.; Kurmanbayeva, A.; Janibyek, T. (Farabi Journal of Social Sciences, 2020)
Journalism is transformed, there is an aggravated balance of the proportion of time and space of communication and information dimensions, there is a need to consider the form of the audience in a new way. The actual problems of world journalism, which have achieved freedom in moving away from the vices of ideology and dissemination of information, partially can not move away from the contradictions of human rights, information impartiality. In the context of the new century, the study of information presented by science, the state of its presentation, the identification of negatives and needs, the expected main step from the scientific journalistic Institute. At the same time, the historical method, comparative and expert actions form the basis of the research in the article. Scientific views are valuable because they offer deep approaches to the modern problem of journalism and solutions. Because the methodology of information dissemination is one of the main tasks common to human journalism, which is not divided into races, Nations, genders. The process of post-modernization of traditional genres of journalism in the category of information technology integration into a single information resources, information flow transition to neoclassicism, the growing number of scandals manipulative messaging and technological letter futuristic primitive, carefree, poor journalistic analysis it is not a secret. In addition, in the twenty-first century, there have been frequent violations of the rules of ethics in the media. For example, the state of monitoring and compliance with high standards in the news and media has been neglected, and theoretical and moral reintegration, ethical and professional competence have become commonplace in the field of journalism. Key words: journalism, new media, convergent journalism, information, human, ideology